Wash day in Trinidad - (:unkn) unknown (My University, 2009)
Women washing by the river.
Colour:Black and white;Style:Landscape;Other:Unbordered,Undivided
Keywords: Postcards; Trinidad and Tobago; East Indian--Women; Laundry; Rivers